2012 IEEE 15th International Symposium on Design and Diagnostics of Electronic Circuits &Amp; Systems (DDECS) 2012
DOI: 10.1109/ddecs.2012.6219053
|View full text |Cite
|
Sign up to set email alerts
|

OBIST strategy versus parametric test - Efficiency in covering catastrophic faults in active analog filters

Abstract: This paper deals with the comparison of the fault coverage of catastrophic faults in active analog integrated filter obtained by the measurement of filter parameters and by the Oscillation-based Built-In Self Test (OBIST) approach. In our experiment, firstly, the cut-off frequency, ripple in the pass band, DC gain in pass band and group delay of the filters have been monitored in the operating mode. Then, during the test mode (OBIST), the filter is transformed to an oscillator, and the oscillation frequency is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Similarly to the OBIST system presented in Reference [9], a phase shift between fault-free and faulty circuits could be estimated [35]. In the case of catastrophic fault detection, an on-chip Schmitt oscillator could be used as a reference signal for counting CUT pulses, but such approach cannot be used for the detection of parametric faults [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the OBIST system presented in Reference [9], a phase shift between fault-free and faulty circuits could be estimated [35]. In the case of catastrophic fault detection, an on-chip Schmitt oscillator could be used as a reference signal for counting CUT pulses, but such approach cannot be used for the detection of parametric faults [28].…”
Section: Discussionmentioning
confidence: 99%
“…The n and k bit-count of the digital blocks are calculated as per Equations (3) and 4 As a reference clock for the OBIST system, either an internal Schmitt trigger or external reference oscillator, such as PLL or off-chip oscillator, can be used. A Schmitt internal reference oscillator is mainly used in case of detecting catastrophic faults because its oscillation frequency depends on variations of passive components, which are both used in CUT and reference oscillator [28]. The main drawback of the usage of the internal reference oscillator is a limited usability in detection of parametric faults, since the oscillation frequency of both the CUT and the reference oscillator varies and the probability of a false-positive result increases.…”
Section: Oscillation-based Built-in Self-test Proceduresmentioning
confidence: 99%
“…However, accuracy and the practical application of this method depend on the type of describing function. In [1,4,6,[18][19][20], it has been demonstrated that in the most cases (from the test efficiency point of view), shorts represent the hardest detectable faults when considering application of the oscillation test. This is due to the fact that short faults with a high value of the short resistance do not have a substantial influence on the CUT parameters.…”
Section: Related Workmentioning
confidence: 99%